A Novel Nonlinear Plus Integral Controller With a Real-Time Application on Incubator Temperature Regulation - ONAT, MUSTAFA (My University, 2022)
A gel card incubator is a significant clinical interface device that brings the gel card’s temperature up, and maintains it at body temperature, and completes the initial step in determining the blood grouping. Achieving a much faster closed-loop response to shorten the warm-up period and maintaining a uniform temperature inside the incubator are crucial requirements for medical incubation devices. To accomplish the incubator control requirements and deal with dead time, this study proposes a novel nonlinear plus integral control (NPI) scheme coupled with a time-delay compensator using an incubator dynamics model. The NPI successfully shaped the control structure by utilizing a few nonlinear parameters. The control strategy, which promises significant performance by combining linear and nonlinear control actions, is easy to realize, simple to tune, and allows smooth transition between control actions. Experiments were performed in a microprocessor-controlled gel card incubator by using a computer interface to demonstrate the superiority of the proposed control technique. The comparative results prove that the proposed control scheme exhibits superior responses for transient and steady states. It also achieves successful disturbance rejection and less energy consumption than the Smith predictor-based proportional integral (PI) control.
Keywords: Elektrik-Elektronik Mühendisliği; Diğer; Mühendislik ve Teknoloji; Electrical and Electronics Engineering; Other; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Mühendislik; MÜHENDİSLİK, ELEKTRİK VE ELEKTRONİK; Engineering, Computing & Technology (ENG); ENGINEERING; ENGINEERING, ELECTRICAL & ELECTRONIC; Elektrik ve Elektronik Mühendisliği; Sinyal İşleme; Fizik Bilimleri; Electrical and Electronic Engineering; Signal Processing; Physical Sciences; Body temperature; gel card incubator; nonlinear plus integral controller; Smith predictor; temperature control.